Effects of heat on new and aged polyamide 6,6 textiles during pest eradication - Richardson, E.; Martin, G.; Wyeth, P. (Polymer degradation and stability, 2014)
Subjecting artefacts to raised (58 °C) or lowered (−30 °C) temperatures in order to combat the problem of pest infestations is common practice within the museum and heritage sector. However, concerns have been raised by the conservation profession about applying temperature based pest treatments to polyamide 6,6, due to the changes in thermal properties known to occur over the range of temperatures in question. Unaged and artificially aged polyamide 6,6 fibres were subjected to creep/recovery experiments using dynamic mechanical analysis at temperatures ranging from 58 °C to −30 °C. These experiments were carried out on loaded samples to determine whether textile material would suffer deterioration if treated whilst hanging under load, for example on a mannequin. Samples were analysed before and after loading by attenuated total reflectance Fourier-transform infrared spectroscopy, differential scanning calorimetry and tensile testing to investigate the chemical and physical alterations in the polyamide 6,6 fabric subject to treatment. Samples loaded at room temperature exhibited permanent contraction, attributed to strain induced crystallization. For both the unaged and aged samples at elevated temperatures the samples underwent permanent deformation. Samples treated at sub-ambient temperatures recovered to their original length during the recovery section of the creep test, although some structural alterations were evident during subsequent analysis. The results suggest that the low temperature treatments of polyamide artefacts, particularly in the presence of stress, are preferable.